Comparing the theory of planned behavior and transtheoretical model in limiting screen time before bedtime: a narrative review - Zerin, Farhana F.; Hegazy, Hadeer; Akter, Nasrin; Banu, Bilkis; Bithi, Sonia J.; Kanta, Fatema Arefin (International Journal of Research in Medical Sciences, 2025)
Excessive screen time before bed is becoming an increasing public health issue, as it’s associated with poor sleep, impaired cognitive functioning, and elevated stress levels. The key to healthier digital habits is understanding behavior change mechanisms. The purpose of this article is to compare the theory of planned behavior (TPB) and the transtheoretical model (TTM) to determine their relative effectiveness for screen use reduction prior to sleep. TPB describes behavior change in regards to attitudes, subjective norms and perceived behavioral control; however, it also faces struggles with the intention-behavior gap, where individuals intend to reduce screen use but fail to act. In contrast, TTM recognizes that behavior change is a multi-stage process, allowing for tailored interventions based on an individual’s readiness for change. This narrative review attempts to synthesize empirical research on TPB and TTM in a systematic literature search in ISI Web of Science, Scopus, PubMed, SID and Magiran. Studies were included if they focused on screen time reduction and applied either TPB or TTM. The review emphasizes that TPB gives insightful understanding of behavioral intentions, while TTM provides a step-by step, structured framework for intervention development. Findings suggest that integrating TPB’s predictive strengths with TTM’s staged framework could enhance intervention effectiveness. Future research should explore hybrid models that bridge the gap between intention formation and sustained behavior change, ultimately supporting better sleep hygiene and long-term digital well-being.